Critical issues and pitfalls in serum and plasma handling for complement analysis in nanomedicine and bionanotechnology. (June 2022) - Moghimi, S. Moein; Simberg, Dmitri
Abstract: The complement system is a group of soluble and membrane-bound proteins belonging to the innate arm of the immune system, offering protection against intruders, including drug delivery systems, as well as regulating host homeostasis. However, when uncontrolled, complement activation could trigger inflammatory reactions. Considering these, careful assessment of complement activation by particulate medicines becomes important, since over activation of the complement system could negatively impact their therapeutic potential. For careful complement analysis, meticulous handling and characterisation of sera/plasma is needed but regularly omitted by the research community. Here, we draw attention to this problem and call for implementation of quality assessment guidelines in sera/plasma preparation, storage and validation. We further highlight critical and variable biological factors that affect complement evaluation. These measure are necessary for reproducible complement mapping and for eliminating erroneous conclusions on complement evasion/activation properties of investigational and regulatory-approved particulate medicines. Graphical Abstract: ga1